Age-Related Decrease in Heat Shock 70-kDa Protein 8 in Cerebrospinal Fluid Is Associated with Increased Oxidative Stress - Loeffler, David A.; Klaver, Andrea C.; Coffey, Mary P.; Aasly, Jan O.; LeWitt, Peter A. (Frontiers in Aging Neuroscience, 2016)
Age-associated declines in protein homeostasis mechanisms (“proteostasis”) are thought to contribute to age-related neurodegenerative disorders. The increased oxidative stress which occurs with aging can activate a key proteostatic process, chaperone-mediated autophagy. This study investigated age-related alteration in cerebrospinal fluid concentrations of heat shock 70-kDa protein 8 (HSPA8), a molecular chaperone involved in proteostatic mechanisms including chaperone-mediated autophagy, and its associations with indicators of oxidative stress (8-hydroxy-2’-deoxyguanosine [8-OHdG] and 8-isoprostane) and total anti-oxidant capacity. We examined correlations between age, HSPA8, 8-OHdG, 8-isoprostane, and total antioxidant capacity in CSF samples from 34 healthy subjects ranging from 20 to 75 years of age. Age was negatively associated with HSPA8 (rho = -0.47; p = .005). An age-related increase in oxidative stress was indicated by a positive association between age and 8-OHdG (rho = 0.61; p = .0001). HSPA8 was moderately negatively associated with 8-OHdG (rho = -0.58; p = .0004). Age and HSPA8 were weakly associated with 8-isoprostane and total antioxidant capacity (range of rho values: -0.15 to 0.16). Our findings in this exploratory study suggest that during healthy aging, cerebrospinal fluid HSPA8 may decrease, perhaps due in part to an increase in oxidative stress. Our results also suggest that 8-OHdG may be more sensitive than 8-isoprostane for measuring oxidative stress in cerebrospinal fluid. Further studies are indicated to determine if our findings can be replicated with a larger cohort, and if the age-related decrease in HSPA8 in cerebrospinal fluid is reflected by a similar change in the brain.